Counselling psychology in the United States. Issue 2 (2nd April 2016) - Lichtenberg, James W.; Goodyear, Rodney K.; Hutman, Heidi; Overland, Emily A.
Abstract : Counseling psychology (CP) emerged in the US as the result of the convergence of a number of trends in early applied psychology, a number of social factors, as well as changes in the organizational structure of the American Psychological Association. We offer an overview of the history of counseling psychology in the US, focusing on key events that have helped establish and shape the profession. Struggles over the definition of CP as a specialty and its relations with clinical psychology and professional counseling are discussed, as are matters related to the licensing of CP practitioners, and the profession's relationships with counseling-related professional organizations. The educational and professional preparation of CPs, the profession's core values that affect both training in and the practice of counseling psychology, and the settings in which CPs work are briefly described. We close with a discussion of several of the challenges facing CP as it is organized and institutionalized in the US.